Reconstructing Kobe : The Geography of Crisis and Opportunity - Edgington, David W., 1950- (Book collections on Project MUSE., 2010)
Six thousand people died and hundreds of thousands lost their homes when the Great Hanshin Earthquake hit Kobe in January 1995. It was the largest disaster to affect postwar Japan and one of the most destructive postwar natural disasters to strike a developed country. Although the media focused on the disaster's immediate effects, the long-term reconstruction efforts have gone largely unexplored. Drawing on fieldwork and interviews with planners, activists, and bureaucrats, David Edgington records the first ten years of reconstruction and recovery efforts and offers detailed descriptions of the geography of crisis and opportunity. Which districts were most vulnerable to quake and why? Did policy makers and planners exploit opportunities to revitalize the city and make it more sustainable and disaster proof? Edgington's intricate investigation of Japanese urban policy, local governance, and land use in stricken neighbourhoods reveals that Japan's particular style of urban redevelopment hindered rather than hastened its ability to rebuild a devastated city. An absorbing account of the largest urban-planning redevelopment effort in Japanese history and the disaster that caused it, Reconstructing Kobe offers real-world solutions to urban planners and policy makers and is essential reading for students and scholars of Japanese urban and planning history.